Development and evaluation of an electronic signing storybook for enhancing reading among deaf students - Mazlan, Nurul Hijja (2011)
The purpose of this study was to develop and investigate the effect of CODERead, an electronic signing storybook based on print titled Pengembaraan si Kuda Laut to promote reading skills among deaf students. This quasi-experimental study specifically investigated its impact on vocabulary among deaf respondents. Ten deaf students (M = 11.3 years old) from government-funded deaf school in Kuala Lumpur were involved in this study. Respondents were assigned to two groups; treatment, in which they received CODERead reading sessions and control group, who received the conventional dialogic reading sessions. Descriptive statistic and nonparametric;Wilcoxon Sign Rank Test and Mann-Whitney U Test were used to compute the quantitative data. Results indicated that CODERead successfully improved deaf students’ written word recognition (WWR) and written word meaning (WWM) but not signed word recognition (SWR). By identifying effects of CODERead on deaf's vocabulary, it will allow for more effective technology integration on the deaf literacy and may direct for more future research on the deaf educational technology field.